Eoldist, a Web Application for Estimating Cautionary Detection Distance of Birds by Automatic Detection Systems to Reduce Collisions With Wind Turbines - Julie Fluhr; Olivier Duriez; Constance Blary; Thierry Chambert; Bettina Almasi; Patrik Byholm; Nelleke H. Buitendijk; Jocelyn Champagnon; Mindaugas Dagys; Wolfgang Fiedler; Charlotte Francesiaz; Frédéric Jiguet; et al. (Wind Energy)
ABSTRACT The installation of automatic detection systems (ADSs) on operating wind energy facilities is a mitigation measure to reduce bird collisions. The effectiveness of an ADS depends on a combination of parameters, including the detection distance of the bird, its flight speed, and the time to complete the chosen action (e.g., turbine shutdown). We created a web application, Eoldist, to calculate cautionary detection distances required by an ADS, using bird flight speed and turbine shutdown time as input parameters. We compiled a database of the flight speeds of 168 Western Palearctic birds from a review of scientific literature supplemented by an analysis of unpublished GPS‐tracking datasets. To estimate turbine shutdown time, we conducted 137 field trials of experimental shutdown at seven wind farms and found that the duration to reach residual rotor speeds of 3 or 2 rotations per minute (rpm) was respectively 32.2 or 38.8 s on average. Based on this data, Eoldist allows the user to select a species from the database, wind turbine characteristics, and a residual rotor speed (3 or 2 rpm); it then calculates the time to reach the selected threshold and provides a distribution curve for the cautionary detection distance needed to prevent collision. This article includes examples of cautionary detection distances required for several species to demonstrate the sensitivity of key input parameters. Eoldist is freely available and should help the wind energy industry, ADS suppliers, and environmental agencies to define requirements for ADS bird detection that are compatible with the biology of the target species.